HUBUNGAN USIA MENARCHE DENGAN KEJADIAN MENOPAUSE DI DESA RAMBAH TENGAH HILIR - Fitria, Rahmi (Jurnal Martenity and Neonatal, 2019)
Menarche first menstruation is often the case in the age range of 10-16 year or early in a juvenile central puberty before entering the reproductive season.Menopause is the end of biological processes of the menstrual cycle, the occurrence of a change that because the hormone decreased production of hormones estrogen produced by the ovary.Factors influencing the menopause is age menarche, the number of children, the birth last, and smoking habit, contraceptive users , workload there is a relationship with the menopause menarche ( ), first menstruation the early menarche to come so will be slow or old menopause timbul.data health agency rokan upstream years 2012, obtained in 21 usila number of women are starting from age until 45 & gt; 3.548. 70 years were theThe purpose of this research is he the menarche age as the menopause are village central rambah. downstreamThe kind of research quantitative analytic design research is the approach used cross sectional.The population and included in this study and the rest of 110. soulThe sample tekhnik use sampling. saturatedTest correlation pearson product moment with the menarche age as the menopause in middle village rambah. downstreamObtained the p value 0,0001 ( & it; 0,05 ), relations show that there is the link being ( 0,04 ).Advice for health workers health workers is expected to improve information to women with menarche slow to provide counseling earlier about the premenopause and symptoms and how to delay the menopause.